The long-term impact of the COVID-19 pandemic on primary and specialized care provision and disease recognition in Germany - Platen, Moritz; Bohlken, Jens; Hoffmann, Wolfgang; Kostev, Karel; Michalowsky, Bernhard (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic and the imposed lockdowns severely affected routine care in general and specialized physician practices. Objective: To describe the long-term impact of the COVID-19 pandemic on the physician services provision and incident disease recognition in German physician practices and perceived causes for the observed changes. Design: Observational study based on medical record data and survey data of general practitioners and specialists' practices. Participants: 996 general practitioners (GPs) and 798 specialist practices serving 6.1 million patients for medical record data analyses and 645 physicians for survey data analyses. Main Measures: Within the medical record data, consultations, specialist referrals, hospital admissions, and documented incident diagnoses were extracted for the pandemic (March 2020 – September 2021) and compared to corresponding pre-pandemic months in 2019. The additional online survey was used to assess changes in practice management during the COVID-19 pandemic and physicians' perceived main causes of affected primary and specialized care provision. Main results: Hospital admissions (GPs:-22% vs. specialists:-16%), specialist referrals (-6% vs. -3%) and recognized incident diseases (-9% vs. -8%) significantly decreased over the pandemic. GPs consultations initially decreased (2020: -2%) but compensated at the end of 2021 (+3%), while specialists' consultation did not (-1%). Physicians saw changes in patient behaviour, like appointment cancellation, as the main cause of the decrease. Contrary to this, they also mentioned substantial modifications of practice management, like reduced (nursing) home visits (41%) and opening hours (40%), suspended checkups (43%), and delayed consultations for high-risk patients (71%). Conclusion: The pandemic left its mark on primary and specialized healthcare provision and its utilization. Both patient behaviour and organizational changes in practice management may have caused decreased and non-compensation of services. Evaluating the long-term effect on patient outcomes and identifying potential improvements are vital to better prepare for future pandemic waves.